Volcanic morphology of West Mata Volcano, NE Lau Basin, based on high-resolution bathymetry and depth changes - Clague, D A; Paduan, J B; Caress, D W; Thomas, Hans; Chadwick, W W; Merle, S G (Geochemistry, Geophysics, Geosystems, 2011)
High-resolution (1.5 m) mapping from the autonomous underwater vehicle (AUV) D. Allan B. of West Mata Volcano in the northern Lau Basin is used to identify the processes that construct and modify the volcano. The surface consists largely of volcaniclastic debris that forms smooth slopes to the NW and SE, with smaller lava flows forming gently sloping plateaus concentrated along the ENE and WSW rift zones, and more elongate flows radiating from the summit. Two active volcanic vents, Prometheus and Hades, are located ∼50 and ∼150 m WSW of the 1159 m summit, respectively, and are slightly NW of the ridgeline so the most abundant clastic deposits are emplaced on the NW flank. This eruptive activity and the location of vents appears to have been persistent for more than a decade, based on comparison of ship-based bathymetric surveys in 1996 and 2008–2010, which show positive depth changes up to 96 m on the summit and north flank of the volcano. The widespread distribution of clastic deposits downslope from the rift zones, as well as from the current vents, suggests that pyroclastic activity occurs at least as deep as 2200 m. The similar morphology of additional nearby volcanoes suggests that they too have abundant pyroclastic deposits.
Keywords: ROV Jason (Remotely Operated Vehicle)